Soil Science Simplified - Helmut Kohnke; D.P. Franzmeier (New Delhi Scientific International Pvt. Ltd, 2013)
This book include Soil classification, Soil morphology, and Soil and the environment.
Physical Properties Of Soil Chemical Properties Of Soil Plant Growth Nutrition
Keywords: Physical Properties Of Soil; Chemical Properties Of Soil; Plant Growth Nutrition